The Critical Role of Ferroptosis in Hepatocellular Carcinoma - Pan, Fan; Lin, Xinrong; Hao, Liping; Wang, Ting; Song, Haizhu; Wang, Rui (Frontiers in Cell and Developmental Biology, 2022)
Liver cancer is the sixth most frequently diagnosed cancer and the third dominant cause of cancer death worldwide. Ferroptosis is characterized as an iron-dependent form of regulated cell death, with accumulation of lipid peroxides to lethal amounts. Evidences have showed that ferroptosis is closely associated with HCC, but the mechanisms are still poorly understood. In this review, we mainly summarize the roles of several typical molecules as well as radiotherapy in regulating the ferroptosis process in HCC. Chances are that this review may help address specific issues in the treatment of HCC.